SYT11 as a Novel Gene in Congenital Myasthenic Syndromes - Lau, Jarred (Université d'Ottawa / University of Ottawa, 2022)
The congenital myasthenic syndromes (CMS) are a group of rare genetic diseases affecting the neuromuscular junction (NMJ). These syndromes affect signal transmission and result in fatigable muscle weakness. In this study we performed exome analysis of 2 CMS patient cohorts and identified SYT11, a synaptotagmin inhibitor of clathrin mediated endocytosis (CME), and MGAT5B, a glycosylation protein, as potential novel CMS genes using bioinformatic analysis on the RD-Connect Genome Phenome Analysis Platform (GPAP). To validate them, we utilized morpholino knockdown models of zebrafish orthologues syt11a, syt11b, and mgat5b and conducted functional assays measuring chorion activity and escape response. Our results show that co-knockdown of syt11a/b or syt11b alone (and not mgat5b) results in a substantial neuromuscular deficit, with ablation of chorion activity and severely reduced escape response. Immunofluorescent studies showed both motor neuron growth and NMJ formation was inhibited by syt11a/b knockdown. In conclusion, syt11b causes a severe neuromuscular phenotype in zebrafish which supports SYT11 as a novel CMS-causing gene.
Keywords: congenital myasthenic syndromes; novel gene discovery; zebrafish; SYT11; exome; rare disease